42.6k views
5 votes
Predict what would happen to the grap when it went from y=f(x)/g(x) to y= g(x)/f(x), when f(x)=x+1 and g(x)=1 -x^2

User Arnehehe
by
5.0k points

1 Answer

7 votes

We are given that f(x)=x+1 and g(x)=1-x^2.

First, consider that


g(x)=(1\text{ -x)(x+1)}

so, we have that


(f(x))/(g(x))=\frac{x+1}{(1\text{ -x)(x+1)}}

so, whenever x is not -1, we get


(f(x))/(g(x))=\frac{1}{1\text{ -x}}=\text{ -}\frac{1}{x\text{ -1}}

whose graph is like this

however, note that


(g(x))/(f(x))=\frac{(1\text{ -x)(x+1)}}{(x+1)}

so, whenever x is not -1 we have


(g(x))/(f(x))=\text{ -(x -1)}

whose graph looks like this

Predict what would happen to the grap when it went from y=f(x)/g(x) to y= g(x)/f(x-example-1
Predict what would happen to the grap when it went from y=f(x)/g(x) to y= g(x)/f(x-example-2
User Tenmiles
by
4.7k points